Identification of kappa opioid receptors in the immune system by indirect immunofluorescence. - Lawrence, D M (1995)
A method to visualize the kappa opioid receptor is described that uses a high-affinity fluorescein-conjugated opioid ligand and indirect immunofluorescence with the phycoerythrin fluorophore to amplify the signal. The mouse thymoma cell line R1E/TL8x.1.G1.OUAr.1 (R1EGO), which expresses the kappa 1 but not mu or delta opioid receptors, was used as a positive control for fluorescence labeling. A fluorescein isothiocyanate-conjugated arylacetamide (FITC-AA) compound displaying high affinity for the kappa opioid receptor was synthesized. R1EGO cells were incubated with FITC-AA, in the absence or presence of the kappa-selective opioid antagonist nor-binaltorphimine (nor-BNI) as a competitor. By using fluorescence microscopy and flow cytometry, incubation of R1EGO cells with FITC-AA alone was not sufficient for the detection of specific staining of the kappa opioid receptor. To amplify the FITC-AA fluorescence, the fluorescein served as a hapten for subsequent antibody detection. R1EGO cells were incubated with FITC-AA, followed by biotinylated rabbit anti-fluorescein IgG and extravidin-conjugated R-phycoerythrin. By using this approach, R1EGO cells were stained with phycoerythrin-amplified FITC-AA, and the staining was displaced with nor-BNI. Flow cytometry showed that titrations of both FITC-AA and nor-BNI produced saturable concentration-dependent changes in the median phycoerythrin fluorescence intensity, with optimal staining at 30 microM FITC-AA. Up to 80% of the fluorescence above background was inhibited by nor-BNI. Freshly isolated thymocytes from C57BL/6ByJ mice also showed nor-BNI-sensitive staining with the FITC-AA amplification. This sensitive method of indirect phycoerythrin immunofluorescence can be used to amplify any fluorescein-conjugated opioid ligand for the detection of opioid receptors.